Seven continents. One sky - Vuţoiu, Beatrice Georgiana; Tǎbǎcaru, Maria Bianca; Beşchea, George Andrei; Câmpean, Ştefan Ioan; Bulmez, Alexandru Mihai; Nǎstase, Gabriel (Frontiers in Climate, 2024)
This paper explores the global impacts of climate change and pollution across diverse regions, highlighting unique challenges and innovative initiatives. From rising temperatures and severe droughts in Africa and Australia to melting glaciers in the Arctic and pollution in Asia, each continent faces significant environmental threats. Despite these challenges, countries are making strides in renewable energy, conservation, and community-based actions. International agreements and local indigenous practices play vital roles in these efforts. The paper concludes with a call for continued global cooperation and local action, emphasizing the potential for a sustainable future through collective innovation and resilience-building. Through this comprehensive analysis, the paper underscores the urgency and possibility of addressing global warming and pollution for a healthier planet.